Comparison of Dentoalveolar Changes with Miniscrew-Assisted Versus Conventional Rapid Palatal Expansion in Growing Patients: A Systematic Review and Meta-Analysis - Hwang bin Lee; Jong-Moon Chae; Jae Hyun Park; Na Jin Kim; Sung-Hoon Han (Applied Sciences)
Background: This meta-analysis aimed to evaluate the dentoalveolar changes of miniscrew-assisted rapid palatal expansion (MARPE) compared with conventional rapid palatal expansion (CRPE) in growing patients (≤16 years). Methods: A systematic and comprehensive literature search was carried out independently by two reviewers using both MeSH terms and free-text keywords across PubMed, the Cochrane Library, and Embase, with studies published through February 2025 included. The risk of bias was assessed using the Cochrane ROB 2.0 tool. The GRADE system was employed to determine evidence quality. Results: Of the 462 initially screened articles, 6 met the inclusion criteria and were selected for quantitative synthesis. Most studies had a low risk of bias with some concerns in reporting. The pooled standardized mean difference (SMD) for tooth inclination changes in CRPE compared with MARPE was 0.98 (95% confidence interval (CI), 0.54 to 1.42; p < 0.01). The test for overall effect was significant (p < 0.01), but no significant differences were found between the subgroups. The pooled SMD for buccal bone thickness changes in CRPE compared with MARPE was 0.69 (95% CI, 0.37 to 1.00; p < 0.01). The test for overall effect was significant (p < 0.01), and there were substantial differences between the subgroups. The supporting evidence ranged in certainty from moderate to low. Conclusions: MARPE was more effective than CRPE in minimizing the buccal tipping and buccal bone loss of the maxillary first premolars and first molars. However, to further confirm these outcomes and guide evidence-based clinical practice, well-designed randomized controlled trials with long-term follow-up are necessary.